Ceremonial Transformation: The Significance of Renaming Memorial Hall after Sarah Baartman at the University of Cape Town (Journal of Student Affairs in Africa, 2022)
At the end of 2018, the University of Cape Town renamed its prominent Memorial Hall after Sarah Baartman, which signalled a significant contribution towards transformation endeavours for the institution. This article is a critical literature review of institutional transformation and practice at UCT which examines the significance of renaming the Memorial Hall. Relying on already published work, it explores student and staff experiences to argue that renaming buildings without changing the lived experiences of those who occupy such buildings is not enough. Therefore, the article concludes that attempts at transformation need to stop being solely ceremonial and recommends that UCT improve its transformation efforts. A process that will hinge on the interrogation of the non-traditional experiences of those who now occupy the buildings during and after the renaming processes, especially for buildings as significant as the Memorial Hall.